Job embeddedness in Icelandic labor market : the effectiveness on turnover intentions and job performance - Helga Gunnólfsdóttir 1986- (2016)
Job embeddedness is a relatively new construct that Lee, Mitchell and colleagues started researching in 1995 (Lee, Burch, and Mitchell, 2014). That construct explains why people stay in their current jobs. A questionnaire was sent to a sample of random emails found on websites of 183 of the 300 biggest companies in Iceland. I sent out a total of 5748 emails to employees and received 1282 replies (22.3% answer rate). Not all participants answered all the questions concerning job embeddedness, but a total of 1135 did so, giving a final of 19.8% answer rate. There were a total of 8 hypotheses in the study, the first one regarding distinct job embeddedness from work engagement. The second one stated that gender would not affect job embeddedness; hypotheses 3, 4, 5, and 6 were about the effect of age, education, job tenure, and size of a company having effect on job embeddedness. Hypothesis 7 was about job embeddedness describing turnover intentions, and finally hypothesis 8, whether job embeddedness had an effect on job performance. The results showed that hypothesis 1, 3, 5, 7, and 8 were supported, gender had an effect on job embeddedness, but education and size of the company did not. Starfsfesta (job embeddedness) er tiltölulega nýtt hugtak sem Lee, Mitchell og félagar byrjuðu að rannsaka árið 1995 (Lee, Burch og Mitchell, 2014). Þetta hugtak útskýrir af hverju starfsmenn haldast í starfi sínu. Sendur var út spurningalisti á veföng sem valin voru af handahófi frá 183 fyrirtækjum af 300 stærstu fyrirtækjum á Íslandi. Send voru út á 5748 veföng og voru 1282 sem svöruðu (22.3% svarhlutfall). Það voru hinsvegar ekki allir þátttakendur sem svöruðu öllum spurningum tengdum starfs festu, eða 1135 sem gerði 19.8% loka svarhlutfall. Það voru 8 tilgátur settar fram í rannsókninni, fyrsta var hvort starfsfesta og helgun í starfi (job engagement) séu lík en samt sitthvor hugtökin. Önnur tilgátan var um að kyn hefði ekki áhrif á starfsfestu; tigátur 3, 4, 5 og 6 voru um að aldur, menntun, fjöldi ára í starfi og stærð ...